Promoting the industrial heritage: an example of recovery of the area ex- S.A.R.O.M. on the dock of Ravenna: Preserving and revitalizing industrial heritage: the case of ex-S.A.R.O.M. area in Ravenna (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Countless are abandoned industrial buildings that dominate the skyline of today's urbanizedareas and which, thanks to their imposing size, have now become part of all those intrinsiccharacteristics that make up the identity of a place. For many, these buildings are part of a historicalmoment that saw them as a symbol of progress and wealth, but following the awareness of planetarypollution and the need to reflect on the theme of environmental protection, the situations in which theseindustrial complexes have been abandoned have become increasingly common. To prevent thesebuildings from being left in a state of neglect, a mere memory now without function, how to redeem themgiving industrial buildings a new life in the changing society? Often a demolition and reconstructionprocess deprives a place of its collective identity, which could instead be maintained in a strategicoperation of “adaptive reuse”. Will be proposed a reflection on some examples of the successfulredevelopment of industrial complexes in Europe will be illustrated a study of the regeneration of theindustrial area ex-SAROM on the dock of the city of Ravenna, aimed at the integration of its two coolingtowers into a multifunctional park. The Hammon towers, visible from every point of the city, havebecome for the inhabitants an essential landmark, but they are located within the disused factory areawhich makes their integration impossible into everyday urban life, giving us an ideal example to work on.